1989
DOI: 10.1210/endo-125-1-192
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of Renal Mineralocorticoid Receptors with an Antiserum against a Peptide Deduced from the Complementary Deoxyribonucleic Acid Sequence

Abstract: We have synthesized three peptides corresponding to putative antigenic regions in the immunogenic domain, hinge region, and carboxy-terminus of the protein. A rabbit immunized with a peptide derived from the hinge region of the receptor produced an antiserum which showed 50% displacement with 20 pg peptide at a final serum dilution of 1:35,000. When the antiserum was immunopurified and applied to sections of intact rat and human kidney it stained cells lining segments corresponding to distal tubule, connecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
38
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(44 citation statements)
references
References 42 publications
6
38
0
Order By: Relevance
“…Immunoreactive precipitates were consistently observed in both cytoplasm and nucleus of the epithelial cells of renal tubules and of those of several exocrine glands under various conditions in agreement with the reports of Krozowski et al (1989) and Rundle et al (1989). In the colonic columnar cells as well as renal tubular cells, the cytoplasmic localization of MR may reflect a non-genomic action of the receptor such as association with unknown factors proximally or distally involved in sodium transport.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Immunoreactive precipitates were consistently observed in both cytoplasm and nucleus of the epithelial cells of renal tubules and of those of several exocrine glands under various conditions in agreement with the reports of Krozowski et al (1989) and Rundle et al (1989). In the colonic columnar cells as well as renal tubular cells, the cytoplasmic localization of MR may reflect a non-genomic action of the receptor such as association with unknown factors proximally or distally involved in sodium transport.…”
Section: Discussionsupporting
confidence: 87%
“…Mucosa was separated from the muscular layer of the intestine at the time of sampling. Specimens were homogenized in 3 vol of TM buffer which consisted of 10 mM Tris, 60 mM Na2Mo4, and 1 mM dithiothreitol, pH 7.4, and centrifuged at 100,000 x g for 1 hr at 4°C (Krozowski et al 1989). The cytosol (2.5 ml) was mixed with 100 pl of DEAE-Sepharose previously equibrated in TM buffer for 1 hr at 4°C, and centrifuged at 100 X g for 5 sec.…”
Section: Western Blottingmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemical, hormone binding, and RT-PCR studies revealed the MR unambiguously along the ASDN (4,7,10,13,32,37,45,53), but MR localization in upstream nephron portions such as the thick ascending limb (TAL) is less clear. Similarly, a convincing demonstration of MR expression in intercalated cells in the kidney in vivo is lacking.…”
mentioning
confidence: 99%
“…Specimens were frozen immediately after resection and were subsequently stored at -80°C. Specimens were homogenized in 3 vol of TM buffer which consisted of 10 mM Tris, 60 mM Na2Mo4, and 1 mM dithiothreitol, pH 7.4, and centrifuged at 100,000 x g for 1 hr at 4°C (Krozowski et al 1989). The cytosol (2.5 ml) was mixed with 0.1 ml of DEAE-Sepharose previously equibrated in TM buffer for 1 hr at 4°C, and centrifuged at 1,000 x g for 5 sec.…”
Section: Immunohistochemistrymentioning
confidence: 99%